Feeble ring - Sinan O. AL-Salihi; Alaa N. Salman (Tikrit Journal of Pure Science)
An ideal A of a semiring S is called k-ideal if for any two elements r A and x S such that r A, then x Aʺ. This leads us to introduce the new concept feeble ring as generalization of k-ideal. Several basic properties, example and characterization of this concept are given. Moreover, the study investigate relationship of feeble ring with other classes.